دور التندبات المشوهة لعنق الرحم في انبثاق الأغشية الباكر - عبد الرحمن أحمد; الدالي عصام; حاج خليل محمد علي خضر (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة معظم الحوامل الولودات اللواتي راجعن العيادة النسائية بالفترة الممتدة بين 1 / 1/ 2002 حتى 1/ 6/ 2003. حيث تم إجراء الفحص النسائي بالمنظار المهبلي والمس المهبلي. وتم عزل مجموعة الحوامل الولودات اللواتي لديهن تندبات مشوهة على عنق الرحم ومتابعتهن حتى الولادة كان عدد الحوامل الولودات المراجعات للعيادة النسائية واللواتي خضعن للفحص 1025 مريضة. وكان عدد الحوامل اللواتي لديهن ندبة مشوهة على عنق الرحم 75 مريضة وبنسبة تعادل 7.31 %. وكان عدد المريضات اللواتي لديهن ندبة مشوهة على عنق الرحم واللواتي حدث لديهن PROM (انبثاق الأغشية الباكر) يعادل 31 مريضة وبنسبة تعادل 41.33%. وكانت نسبة الـ PROM لدى مجموعة الشاهد والبالغ عددها أيضا 75 مريضة 18.66%. تبين بالدراسة أن معظم حالات انبثاق الأغشية الباكر حدثت لدى المريضات اللواتي لديهن سوابق ولادات منزلية . تبين بالدراسة أن معظم حالات الـ PROM حدثت بعمر حملي <35 اسبوع وكان عددها 8 حالات وبنسبة تعادل 25.80%. لم نجد أي علاقة بين تعدد الولادات الطبيعية وحدوث التندب المشوه على عنق الرحم. We studied most of the multipar who visit the clinic of Cynaecologiy and Obstetric in Alassad Hospitol of Tichreen University between 1/1/2002 and 1/6/2003 . We have examed the patients by vaginoscopy and vaginal examination . We selected the group of patients who have deformed scare in the cervix The number of paitents who has been examed was 1025 patients. The number of Paitents who have deformed scares in the cervix was 75 Patients on 7.31%. PROM (premature rupture of the membranse) has occured in 31 Ptients out of the group with deformed scare on 41. 33%. Comparing with the normal group PROM has occured in (14) Patients on 18.66%. We found that most of the BROM cases have occurred in the patient who had (house deliveries) . We found that most of the PROM cases occure in Pregnantal age [ 35 week They were 8 cases in Percentage (25.80) %. We coundn’t prove any relation between deformed scares the cervix and multi delivery